Dynamics of Legal Protection of Customary Land Rights in Batu Belah Village Kampar Regency - Ricky Musliadi; Mardalena Hanifah; Emilda Firdaus; Muhammad Zulhidayat; Kamilia Amirah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The rights of customary law communities are divided into two, namely individual and communal rights. The land tenure of customary law communities contained in the UUPA is a customary right (territory) to show to the land which is the environmental area of the legal community concerned. One of the problems related to customary land in Batu Belah Village is regarding the boundaries of the land. Unclear customary land boundaries give rise to disputes. The same thing ultimately hinders the process of registering customary land in Batu Belah Village, Kampar Regency. Based on this background, the main issues that the author wants to raise, among others, are first, How is the protection of customary land laws in Batu Belah Village, Kampar Regency? Second, what is the status of customary land in Batu Belah Village, Kampar Regency?, The type of research used by the author is sociological legal research, sociological legal research is also called empirical law research. The results of the study show that Batu Belah Village, Kampar Regency has not been registered because of several constraints. Thus, until now customary land in the region has not had a clear legal basis and is only interpreted on the basis of customary recognition in the sense that it has not received clear legal protection.